2016
DOI: 10.1044/2016_ajslp-15-0038
|View full text |Cite
|
Sign up to set email alerts
|

Language Variation and Theory of Mind in Typical Development: An Exploratory Study of School-Age African American Narrators

Abstract: ToM indicators, such as false-belief mentioning, provide information about African American children's narrative ability and appear to be dialect-neutral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…Although racial differences in narration have been studied since the 1960s, efforts to identify culturally-fair measures of narrative language for AAE speakers are relatively recent. Candidate measures include false-belief mentioning (Mills & Fox, 2016) and rare vocabulary usage (Mills et al, 2017), as they were positively correlated with measures of language productivity and educational placement but not correlated with language variation. Language variation-the extent to which children's language differed from MAE-was measured by the Diagnostic Evaluation of Language Variation-Screening Test (DELV-S; Seymour et al, 2003).…”
Section: Perceptions Of Narrative Languagementioning
confidence: 97%
See 3 more Smart Citations
“…Although racial differences in narration have been studied since the 1960s, efforts to identify culturally-fair measures of narrative language for AAE speakers are relatively recent. Candidate measures include false-belief mentioning (Mills & Fox, 2016) and rare vocabulary usage (Mills et al, 2017), as they were positively correlated with measures of language productivity and educational placement but not correlated with language variation. Language variation-the extent to which children's language differed from MAE-was measured by the Diagnostic Evaluation of Language Variation-Screening Test (DELV-S; Seymour et al, 2003).…”
Section: Perceptions Of Narrative Languagementioning
confidence: 97%
“…Hence, raters listened to two narratives elicited under differing visual conditions (no visual = personal narrative, visual = five-picture sequence narrative). We chose to include narratives elicited from no visual and from a five-picture sequence for efficiency of listening because the two conditions yielded narratives of relatively short length compared to a wordless book (Mills, 2015b;Mills & Fox, 2016), reducing the listening time required of each adult rater.…”
Section: The Current Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Across cultures, narratives are listened to and spoken by children and by people in children's speech communities (Berman & Slobin, 1994;Curenton, 2010;McCabe, 1997;Melzi, 2000). Furthermore, recent studies have identified dialectneutral indices of narrative language, such as internal-state vocabulary, on which child speakers of MAE and NMAE varieties do not differ (Burns, de Villiers, Pearson, & Champion, 2012;Mills & Fox, 2016). Furthermore, recent studies have identified dialectneutral indices of narrative language, such as internal-state vocabulary, on which child speakers of MAE and NMAE varieties do not differ (Burns, de Villiers, Pearson, & Champion, 2012;Mills & Fox, 2016).…”
mentioning
confidence: 99%